ON THE LINES OF RESEARCH OF ORIGIN OF THE SARYKUM BARCHAN DUNES - V. U. Matsapulin; E. V. Tulysheva; M. V. Khlopkova (Юг России: экология, развитие)
Aim. The main aim of the research is to show the groundlessness of critical remarks and their bias, shortcomings and misconceptions in the study of Sarikum, ways to address the origin of the Sarykum dunes.Methods. Critical analysis of publications, own analytical studies of the carbonate crust material and a system analysis of the proposed solutions are used as basic methods for the present study.Findings. Analysis and processing of additional analytical data confirmed earlier conclusions about the endogenous origin of the carbonate crusts of Sarikum. Thus, the study showed the prospects of using geochemical studies of carbonate and gypsum veinlets.Conclusion. Two approaches are shown in solving the problems of the origin of the Sarykum eolian bodies. The most promising approach is the recognition of the Late Cenozoic volcanism in the valleys of watercourses from the south of Sarykum and the antecedent development of the river valleys of the Eastern Caucasus and, in particular, the valleys cutting the Narat-Tube ridge.